From nabeeld to kopie: the after-image and the copy in Early Modern Netherlandish art. Issue 3 (3rd July 2019) - Wouk, Edward H.
Abstract: This article examines the emergence and transformation of the 'copy' as a category of image in sixteenth-century Netherlandish art and art-writing. It attends to a vocabulary that existed before, and then coexisted alongside, the arrival of the word kopie (from the French copie ) in an incipient vernacular discourse on Netherlandish art. When the painter and poet Lucas d'Heere introduced the term kopie into Dutch in relation to Michiel Coxcie's copy of the Van Eyck brothers' Ghent Altarpiece in a poem of c .1559, he highlighted the novelty of this self-conscious replica. For d'Heere, Coxcie's copy aligned closely with his own project to evaluate the history of Netherlandish art from its perceived origins in the work of the Van Eycks to its modern development in print publishing houses and large studios such as that of his master, the painter Frans Floris. By considering the roles that copies played in cultures of artistic creation and collecting, this article draws attention to the institutionalization of the copy and the formation of artistic canons. It addresses the secularization of images as well as the advent of new artistic categories in response to the rise of printed multiples and the art market.